Late-Night Use of Social Media and Cognitive Engagement of Female Entrepreneurs: A Stressor–Strain–Outcome Perspective. (August 2021) - Shahzad, Fakhar; Abbas, Adnan; Fateh, Adnan; Kasim, Raja Suzana Raja; Akram, Kashif; Ashraf, Sheikh Farhan
The excessive use of social media is an emerging phenomenon with several negative consequences in an entrepreneurial context. Based on the stressor–strain–outcome paradigm, this research aims to unveil the following: that social media late-night usage can affect two psychological strains (life invasion and technostress) among female entrepreneurs and thus influence their behavioral outcome (cognitive engagement). This study empirically tested the proposed mediation model using an online survey of 225 female entrepreneurs from the small- and medium-sized enterprise sector. A partial least squares structural equation modeling (PLS-SEM) was implemented to obtain the results. The findings indicate that late-night social media usage significantly raises life invasion and technostress among female entrepreneurs. Moreover, internal strains (life invasion and technostress) reduce female entrepreneurs' cognitive engagement and significantly mediate the association between late-night use of social media and entrepreneurial cognitive engagement. This study draws associated practical and theoretical contributions based on findings, which were not previously discussed.